Stop to smell the virtual roses: a mixed-methods pilot study on the impact of multisensory virtual reality nature experiences on feelings of relaxation - Lopes, Marilia Karla Soares; De Jesus, Belmir Jose; Rosanne, Olivier Manuel; Pardini, Susanna; Appel, Lora; Smith, Christopher; Falk, Tiago Henrique (Frontiers in Virtual Reality, 2024)
This study aimed to investigate the psychological and physiological impacts of audio-visual (AV) and audio-visual-olfactory (AVO) stimuli within an immersive virtual nature environment. Twentytwo nurses from the mental health in-patient ward of a Canadian hospital participated in the study.Each participant chose one of the three available immersive scenarios (beach, lake, waterfall) to experiment with under the AV and AVO conditions. Psychological assessments were conducted via questionnaires to investigate relaxation levels and other measures of user experience.Although the AVO condition demonstrated the greatest improvement in relaxation relative to baseline, no significant differences were observed either between the conditions or across the scenarios. Physiological metrics were collected using an in-house instrumented Oculus Quest 2 virtual reality (VR) headset that allowed us to investigate brain activity via electroencephalography (EEG). Results show a significant difference between the two conditions in certain brain regions.Significant differences in neural patterns were also seen for the participants who reported improvements in relaxation, relative to those who did not report any improvements. For these latter-referenced participants, decreased relaxation resulted from the non-congruence of the presented smells with participant expectations. Furthermore, neuromarkers measured from the EEG, such as frontal alpha asymmetry (a measure of approach/withdrawal), engagement score, as well as valence and arousal indices suggested increased relaxation levels in the AVO condition. Our results suggest that multisensory immersive experiences can impact both physiological and psychological outcomes, resulting in increased relaxation levels and enhanced sense engagement for certain scenes. The instrumented VR headset enabled the monitoring of user neural and behavioural patterns, thus allowing for new insights to be gained beyond those achievable with only questionnaires.1 Lopes et al.